2015
DOI: 10.1155/2015/158794
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Theoretical Decomposition Enthalpies for Predicting Thermal Hazards

Abstract: Much effort is currently put into the development of models for predicting decomposition enthalpies measured using differential scanning calorimetry (DSC). As an alternative to the purely empirical schemes reported so far, this work relies on theoretical values obtained on the basis of simple assumptions. For nitroaromatic compounds (NACs) studied in sealed sample cells, our approach proves clearly superior to previous ones. In contrast, it correlates poorly with data measured in pin-hole sample cells. Progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Unlike our previous study, the highly symmetrical structure of A-OC n reduces the influence of molecular mismatch between the adjacent molecules. , In particular, the disubstitution of anthraquinonoid enhances the molecule–molecule and molecule–substrate interactions, so that ordered self-assembly monolayers can be observed with shorter chain ( n = 7) on the highly oriented pyrolytic graphite (HOPG) surface, which is significant for not only exploring the characters of the short chain but also facilitating the preparation of single crystals. DSC measurements of these A-OC n ( n = 3–18) reveal the variation of melting points and reflect the strength of the intermolecular interactions . Furthermore, in order to get a profound understanding of chain length effects in crystal packing, the Hirshfeld surface analysis and decomposition of interaction energy combined with energy framework have been exploited based on the crystal structures of these A-OC n ( n = 1, 3–6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike our previous study, the highly symmetrical structure of A-OC n reduces the influence of molecular mismatch between the adjacent molecules. , In particular, the disubstitution of anthraquinonoid enhances the molecule–molecule and molecule–substrate interactions, so that ordered self-assembly monolayers can be observed with shorter chain ( n = 7) on the highly oriented pyrolytic graphite (HOPG) surface, which is significant for not only exploring the characters of the short chain but also facilitating the preparation of single crystals. DSC measurements of these A-OC n ( n = 3–18) reveal the variation of melting points and reflect the strength of the intermolecular interactions . Furthermore, in order to get a profound understanding of chain length effects in crystal packing, the Hirshfeld surface analysis and decomposition of interaction energy combined with energy framework have been exploited based on the crystal structures of these A-OC n ( n = 1, 3–6).…”
Section: Introductionmentioning
confidence: 99%
“…DSC measurements of these A-OC n (n = 3−18) reveal the variation of melting points and reflect the strength of the intermolecular interactions. 35 Furthermore, in order to get a profound understanding of chain length effects in crystal packing, the Hirshfeld surface analysis and decomposition of interaction energy combined with energy framework have been exploited based on the crystal structures of these A-OC n (n = 1, 3−6). With the help of STM, the polymorphism of 2D selfassembly and packing efficiency depending on chain length have been investigated for A-OC n (n = 7−18).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, whenever an explicit mechanism of action (MOA) has been presented, it is usually worthwhile to take it into consideration, using a physics-based mathematical modeling rather than an equation derived from a statistical evaluation of candidate variables or formalisms. , While the determination of the relevant mechanisms can be extremely difficult for biological activities or toxicological end points, making assumptions regarding the underlying physics, in principle, is easier for the physicochemical properties of chemicals, because they are not dependent on the complex interactions that characterize biological functions. As a matter of fact, such models based on equations derived from physical considerations have been shown to systematically outperform QSPR methods for many properties, including densities and flash point of liquids, melting points and sublimation enthalpies of crystals, Gurney velocities of explosives, and heats of decomposition of organic substances. …”
Section: Introductionmentioning
confidence: 99%
“…Further studies have indicated that isomerization of nitromethane into nitrite should be taken into consideration, as well as the secondary reactions of the nitro-substituted radicals and the contribution of other primary unimolecular reactions, like isomerization to nitrites and aci-forms . In addition to those methods, the latest development of molecular simulation as a predictive tool, such as, quantitative structure–activity/property relationships, represents an alternative way of predicting physical and chemical properties of energetic materials, like decomposition enthalpies (theoretical decomposition enthalpies). , …”
Section: Introductionmentioning
confidence: 99%
“…43 In addition to those methods, the latest development of molecular simulation as a predictive tool, such as, quantitative structure−activity/property relationships, represents an alternative way of predicting physical and chemical properties of energetic materials, like decomposition enthalpies (theoretical decomposition enthalpies). 44,45 Together with theoretical and computational methods, experimental methods are used to characterize the thermal properties of chemicals, especially for compounds involved in industrial processes. In this context, DSC is one of the most commonly employed techniques to determine inherent chemical reactivity especially because it allows the collection of data with low amounts of material (milligram scale).…”
Section: ■ Introductionmentioning
confidence: 99%